Thirty Years of Minimally Invasive Surgery in Children: Analysis of Meta-Analyses - Schukfeh, Nagoud; Kuebler, Joachim F.; Dingemann, Jens; Ure, Benno M. (European Journal of Pediatric Surgery, 2019)
Introduction In the last three decades, minimally invasive surgery (MIS) has been widely used in pediatric surgery. Meta-analyses (MAs) showed that studies comparing minimally invasive with the corresponding open operations are available only for selected procedures. We evaluated all available MAs comparing MIS with the corresponding open procedure in pediatric surgery.Materials and Methods A literature search was performed on all MAs listed on PubMed. All analyses published in English, comparing pediatric minimally invasive with the corresponding open procedures, were included. End points were advantages and disadvantages of MIS. Results of 43 manuscripts were included. MAs evaluating the minimally invasive with the corresponding open procedures were available for 11 visceral, 4 urologic, and 3 thoracoscopic types of procedures. Studies included 34 randomized controlled trials. In 77% of MAs, at least one advantage of MIS was identified. The most common advantages of MIS were a shorter hospital stay in 20, a shorter time to feeding in 11, and a lower complication rate in 7 MAs. In 53% of MAs, at least one disadvantage of MIS was found. The most common disadvantages were longer operation duration in 16, a higher recurrence rate of diaphragmatic hernia in 4, and gastroesophageal reflux in 2 MAs. A lower native liver survival rate after laparoscopic Kasai-portoenterostomy was reported in one MA.Conclusion In the available MAs, the advantages of MIS seem to outnumber the disadvantages. However, for some types of procedures, MIS may have considerable disadvantages. More randomized controlled trials are required to confirm the advantage of MIS for most procedures.
Keywords: laparoscopy; thoracoscopy; review; meta-analysis; pediatric